2014
DOI: 10.3109/17453674.2014.931197
|View full text |Cite
|
Sign up to set email alerts
|

Faster recovery without the use of a tourniquet in total knee arthroplasty

Abstract: Background and purposeTourniquet application is still a common practice in total knee arthroplasty (TKA) surgery despite being associated with several adverse effects. We evaluated the effects of tourniquet use on functional and clinical outcome and on knee range of motion (ROM).Patients and methods70 patients who underwent TKA were randomized into a tourniquet group (n = 35) and a non-tourniquet group (n = 35). All operations were performed by the same surgeon and follow-up was for 1 year. Primary outcomes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
172
2
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(195 citation statements)
references
References 24 publications
12
172
2
3
Order By: Relevance
“…Quicker ability to achieve this activity was observed in subjects in whom a tourniquet was not used. Ejaz et al [14] [33] in a similar comparative study found no differences in Oxford knee scores at 10 weeks after TKA. To our knowledge, there is no agreed-upon clinically important difference in quadriceps strength for this population.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Quicker ability to achieve this activity was observed in subjects in whom a tourniquet was not used. Ejaz et al [14] [33] in a similar comparative study found no differences in Oxford knee scores at 10 weeks after TKA. To our knowledge, there is no agreed-upon clinically important difference in quadriceps strength for this population.…”
Section: Discussionmentioning
confidence: 97%
“…Increased intraoperative blood loss was observed when a tourniquet was not used, but no statistical differences were found in total (intraoperative + postoperative) blood loss between the tourniquet and no-tourniquet groups. Review of the literature shows the majority of studies confirm that intraoperative blood loss is greater if a tourniquet is not used [3,11,14,17,19,22,28,29,45,49,56,58,60,65]. Reports analyzing total blood loss are conflicting with some demonstrating no differences with or without tourniquet use [1,29,49,58], whereas others demonstrate reduced [3,54] or increased [28,58] total blood loss if a tourniquet is used.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations